WAYS TO SOLUTION THE UNLOADING OF THE TRANSPORT NETWORK IN MODERN CITIES - Buzrukov Zakiryo Sattikhodzhaevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article sets out ways to solve the causes of traffic jams in modern cities of the country of Uzbekistan and shows the main shortcomings of the creation common transport infrastructure and traffic control systems of modern cities. In the course of the study, some ways of resolving issues for correcting traffic jams in cities were recommended .